SIMULASI DAN ANALISA SCHEDULING SERVICE CLASS PADA JARINGAN WIMAX MENGGUNAKAN OPNET MODELER - Ahmad Arif; Helmy Fitriawan; Muhamad Komarudin (Jurnal Informatika dan Teknik Elektro Terapan (JITET), 2013)
Abstract Human need for information now pushing the demand for internet data access speed high rises rapidly. The service offers diverse include text, sound, video, and data. It has become even daily needs that can not be separated from human life. So the need for technology that can deliver voice, data, and video with better quality. This study discusses the application of scheduling service class on data communications applications in the Fixed WiMAX network. Fixed WiMAX network is simulated using OPNET Modeler. Network design performed using a single BS, SS 16 pieces, and the server as a source of traffic. Data is collected for ten minutes. The simulation results obtained show that the application of sound, UGS service class has the greatest value is 3 Mbps throughput and jitter smallest value that is close to 0 s. In video applications, rtPS service class has the greatest value of throughput is 44 Mbps and has the smallest delay value was 0.17 s. On the application file transfer, nrtPS service class has the greatest value is 6,745,187 bps throughput and has the smallest delay value is 0.014 s. In the web browsing application, nrtPS service class has the greatest value is 8.2 Mbps throughput and has the smallest delay value is 0.022 s.Keywords : fixed WiMAX, scheduling service, Opnet Modeler